2002
DOI: 10.1080/13550280290100941
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Function of Class II Major Histocompatibility Complex, CD40, and B7 Expression in Macrophages and Microglia: Implications in Neurological Diseases

Abstract: The ability of microglia, the brain's resident macrophage, to present antigen through the class II major histocompatibility complex (MHC) to T cells allows these normally quiescent cells to play a critical role in shaping the outcome of many neurological diseases. The expression of class II MHC antigens and the costimulatory molecules CD40 and B7 on microglia and infiltrating macrophages is regulated through a complex network of cytokines in the inflamed brain. In this review, we describe the molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 163 publications
1
61
1
Order By: Relevance
“…MHC II ϩ microglial cells have been shown to be an important element in host resistance to cerebral cryptococcosis (21). Activated microglial cells have been demonstrated to engulf C. neoformans and function as APCs by up-regulating MHC class II expression as well as other costimulatory molecules such as CD80, CD86, and CD40 (47) through which they are able to interact with T cells and gain enhanced microbial resistance (47)(48)(49). Therefore, the marked up-regulation of MHC class II expression on microglial cells induced by anti-CD40 and IL-2 treatment in this study indicated that these cells were activated.…”
Section: Discussionmentioning
confidence: 99%
“…MHC II ϩ microglial cells have been shown to be an important element in host resistance to cerebral cryptococcosis (21). Activated microglial cells have been demonstrated to engulf C. neoformans and function as APCs by up-regulating MHC class II expression as well as other costimulatory molecules such as CD80, CD86, and CD40 (47) through which they are able to interact with T cells and gain enhanced microbial resistance (47)(48)(49). Therefore, the marked up-regulation of MHC class II expression on microglial cells induced by anti-CD40 and IL-2 treatment in this study indicated that these cells were activated.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, some latent viruses such as JC virus or varicella zoster produce clinical syndromes mainly in immuno-compromised individuals. MHC and co-stimulatory molecules are strongly increased in CNS infection and a number of CNS pathologic conditions, including ischemia, neoplasm, traumatic nerve injury and neurodegenerative diseases such as AD, PD, MS, HIV-dementia and Creutzfeldt-Jacob disease (Maehlen et al, 1989;McGeer et al, 1993;Graeber et al, 1998;Perry, 1998;Dorries, 2001;Piehl and Lidman, 2001;O'Keefe et al, 2002;Owens, 2002). Recent evidence has implied that the CNS equips itself with a unique defense system with its own molecular and cellular components despite sharing certain properties with the peripheral immune system.…”
Section: Unique Immune Properties Of the Central Nervous Systemmentioning
confidence: 99%
“…7 Once neuronal damage occurs, T cells and antigen-presenting cells (APC) accumulate at lesion sites, with concomitant increased expression of the major histocompatibility complex (MHC) and costimulatory molecules, which are necessary for T-cell activation. [8][9][10][11] It is perceivable that a strict control of the activation of T cells is important to ameliorate their harmful effects on neurons.Optimal activation of T cells by APCs requires at least 2 signals. The first is elicited through recognition of the MHC-peptide complex by T-cell receptor (TCR), and the second is provided by the costimulatory molecules via interaction with their respective receptors on T cells.…”
mentioning
confidence: 99%